EVALUATION OF PLATELET RICH PLASMA (PRP) PREPARATION PROCEDURE - Yuliandari, Aisyara; Damhuri, Prima Octafia; Margaretta, Tiur Sherly; Priskilla, Sarah Ester; Hartini H (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The success of PRP therapy in repairing tissue damage is influenced by the PRP preparation procedure. Currently, there’s no standardization of PRP preparation procedures, and various techniques are used, such as the use of anticoagulants and different centrifugation speeds. This study aimed to evaluating the PRP preparation procedures based on the centrifugations steps (single and double centrifugation) and the use of anticoagulants variation (sodium citrate, EDTA and ACD-A). This study was an experimental study and used blood samples from respondents. The selected respondents must meet inclusion and exclusion criteria. The treatment groups in this study were the single centrifugation group and the double centrifugation group. Each group will be divided into 3 subgroups with different anticoagulant usage (sodium citrate, EDTA and ACD-A). Statistical analysis results showed a significant difference in the mean platelet count in the sodium citrate , EDTA, ACD-A groups with single and double centrifugation steps. Evaluation of platelet preparation procedures in this study, a higher platelet count was obtained, specifically in the sodium citrate group (494 x 103 cells/µL), EDTA group (829.4 x 103 cells/µL), and ACD-A group (607.1 x 103 cells/µL), compared to single centrifugation in the sodium citrate group (354.8 x 103 cells/µL), EDTA group (408.1 x 103 cells/µL), and ACD-A group (390.6 x 103 cells/µL). The highest platelet count in PRP was achieved with the preparation procedure using EDTA as the anticoagulant with double centrifugation. Further research is necessary to evaluate PRP preparation procedures regarding the concentration of growth factors present in PRP.